Theoretical Analysis of The Relationship Between Digital Marketing Activities and Sales Conversion in Business-To-Business E-Commerce Based on The Technology Acceptance Model (TAM) - Sophianie, Noor Emma (Journal Research of Social Science, Economics, and Management, 2026)
This theoretical paper investigates the relationship between digital marketing activities and sales conversion in Business-to-Business (B2B) e-commerce using the Technology Acceptance Model (TAM). It integrates insights from 20 relevant studies published between 2020 and 2025 to develop a comprehensive conceptual understanding of how perceived ease of use (PEOU) and perceived usefulness (PU) shape attitudes (ATU), behavioral intentions (BI), and actual use (AU) in digital marketing adoption. The discussion elaborates on how user perception mediates digital channel effectiveness and highlights TAM's enduring relevance in explaining technology adoption behavior in modern B2B marketing contexts. This theoretical framework aims to enrich academic perspectives and provide strategic insights for practitioners optimizing technology-based marketing systems.